Linking farmer and beekeeper preferences with ecological knowledge to improve crop pollination - Tom D. Breeze; Virginie Boreux; Lorna Cole; Lynn Dicks; Alexandra‐Maria Klein; Gesine Pufal; Mario V. Balzan; Danilo Bevk; Laura Bortolotti; Theodora Petanidou; Marika Mand; M. Alice Pinto; et al. (People and Nature, 2019)
Abstract Pollination by insects is a key input into many crops, with managed honeybees often being hired to support pollination services. Despite substantial research into pollination management, no European studies have yet explored how and why farmers managed pollination services and few have explored why beekeepers use certain crops. Using paired surveys of beekeepers and farmers in 10 European countries, this study examines beekeeper and farmer perceptions and motivations surrounding crop pollination. Almost half of the farmers surveyed believed they had pollination service deficits in one or more of their crops. Less than a third of farmers hired managed pollinators; however, most undertook at least one form of agri‐environment management known to benefit pollinators, although few did so to promote pollinators. Beekeepers were ambivalent towards many mass‐flowering crops, with some beekeepers using crops for their honey that other beekeepers avoid because of perceived pesticide risks. The findings highlight a number of largely overlooked knowledge gaps that will affect knowledge exchange and co‐operation between the two groups. A free Plain Language Summary can be found within the Supporting Information of this article.